Does atypical work help the jobless? Evidence from a CAEAS/CPS cohort analysis - John T. Addison; Christopher J. Surfield (Institute for the Study of Labor (IZA), 2006)
Atypical employment, such as temporary, on-call, and contract work, has been found disproportionately to attract the jobless. But there is no consensus in the literature as to the labour market consequences of such job choice by unemployed individuals. Using data from the Current Population Survey, we investigate the implications of the initial job-finding strategies pursued by the jobless for their short- and medium-term employment stability. At first sight, it appears that taking an offer of regular employment provides the greatest degree of employment continuity for the jobless. However, closer inspection indicates that the jobless who take up atypical employment are not only more likely to be employed one month and one year later than those who continue to search, but also to enjoy employment continuity that is no less favorable than that offered by regular, open-ended employment.
Keywords: 330